Can we draw general conclusions from interval training studies? - Borges Viana, R.; Andre Barbosa de Lira, C. A.; Araújo Naves, J. P.; Silveira Coswig, V.; Boscolo del Vecchio, F.; Ramirez-Campillo, R.; Vieira, C. A.; Gentil, P. (Sports Medicine, 2018)
Interval training (IT) has been used for many decades with the purpose of increasing performance and promoting health benefits while demanding a relatively small amount of time. IT can be defined as intermittent periods of intense exercise separated by periods of recovery and has been divided into high-intensity interval training (HIIT), sprint interval training (SIT), and repeated sprint training (RST). IT use has resulted in the publication of many studies and many of them with conflicting results and positions. The aim of this article was to move forward and understand the studies` protocols in order to draw accurate conclusions, as well as to avoid previous mistakes and effectively reproduce previous protocols. When analyzing the literature, we found many inconsistencies, such as the controversial concept of `supramaximal` effort, a misunderstanding with regard to the term `high intensity,` and the use of different strategies to control intensity. The adequate definition and interpretation of training intensity seems to be vital, since the results of IT are largely dependent on it. These observations are only a few examples of the complexity involved in IT prescription, and are discussed to illustrate some problems with the current literature regarding IT. Therefore, it is our opinion that it is not possible to draw general conclusions about IT without considering all variables used in IT prescription, such as exercise modality, intensity, effort and rest times, and participants` characteristics. In order to help guide researchers and health professionals in their practices it is important that experimental studies report their methods in as much detail as possible and future reviews and meta-analyses should critically discuss the articles included in the light of their methods to avoid inappropriate generalizations.